The Attribute in the Austral Images on the Celestial Medieval Planispheres - Sayáns Gómez, Francisco (Eikón / Imago, 2021)
This work studies and analyzes the attributes of the celestial figures that carry one in the Southern hemisphere of medieval planispheres. The research project undertaken has used as sources exclusively texts from Greek and Latin antiquity that deal with the description of the constellations from the perspective of mythology. These sources define the constellar figures representing the different characters who, due to their particular circumstances, deserved to go up to heaven and remain there for all eternity. The attributes which illustrate the mythological figure holding them, and which are a secondary and subordinate element in the representation to that of the main figure, become the focus of this study. A celestial planisphere is included in order to provide a reference for the location of each figure and its related stars in reference to its companions.